2018
DOI: 10.1016/j.bbi.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and immunity

Abstract: Resilience is the process that allows individuals to adapt to adverse conditions and recover from them. This process is favored by individual qualities that have been amply studied in the field of stress such as personal control, positive affect, optimism, and social support. Biopsychosocial studies on the individual qualities that promote resilience show that these factors help protect against the deleterious influences of stressors on physiology in general and immunity in particular. The reverse is also true… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(132 citation statements)
references
References 163 publications
4
104
0
6
Order By: Relevance
“…Tryptophan metabolites, especially serotonin, have gathered greater attention in the endeavor to understand the pathophysiology of depression . In addition, metabolites of the tryptophan–kynurenine pathway are increasingly attracting interest . Just recently, we reported that plasma tryptophan is a possible diagnostic biomarker of MDD and that some of the tryptophan–kynurenine metabolites in plasma are related to severity of some depressive symptoms .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan metabolites, especially serotonin, have gathered greater attention in the endeavor to understand the pathophysiology of depression . In addition, metabolites of the tryptophan–kynurenine pathway are increasingly attracting interest . Just recently, we reported that plasma tryptophan is a possible diagnostic biomarker of MDD and that some of the tryptophan–kynurenine metabolites in plasma are related to severity of some depressive symptoms .…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43] In addition, metabolites of the tryptophan-kynurenine pathway are increasingly attracting interest. [44][45][46][47][48] Just recently, we reported that plasma tryptophan is a possible diagnostic biomarker of MDD and that some of the tryptophan-kynurenine metabolites in plasma are related to severity of some depressive symptoms. 49 We recently reported that the levels of plasma tryptophan and kynurenine are lower in MDD patients compared to healthy controls, and that especially lower levels of plasma tryptophan are a diagnostic biomarker of MDD.…”
Section: Fourth Step: Pilot Analysis Of Biological Validitymentioning
confidence: 99%
“…The main concept has shifted from haemodynamic changes to neuro-humoral modulation. Most recently, the link between the gut microbiota and HF has drawn more attention (Dantzer, et al, 2018;Moshkelgosha, et al, 2018).…”
Section: Heart Failure and Cardiomyopathymentioning
confidence: 99%
“…In the field of psychoneuroimmunology (PNI), these effects of pro-and anti-inflammatory mediators on the brain and behavior, and the vice versa effects, are the main foci of research (63,(70)(71)(72). Although it is beyond the scope of the present thesis, future research investigating how and which areas in the brain that may elicit, respond to or forward the sickness signals in the sickness behavior circuitry will be of utmost value for the development of our understanding of ME/CFS.…”
Section: Psychoneuroimmunology and Sickness Behaviormentioning
confidence: 99%